An Approximation to Solution of Space and Time Fractional Telegraph Equations by He's Variational Iteration Method. (8th April 2010) - Sevimlican, Ali
Abstract : He's variational iteration method (VIM) is used for solving space and time fractional telegraph equations. Numerical examples are presented in this paper. The obtained results show that VIM is effective and convenient.